Female gender doubles pre-hospital delay times for patients experiencing ST segment elevation myocardial infarction in Saudi Arabia. (1st October 2014) - Alshahrani, Hassan; McConkey, Roy; Wilson, Julie; Youssef, Mostafa; Fitzsimons, Donna
Abstract: Introduction: Pre-hospital delay has a significant impact on patients' mortality and morbidity in ST segment elevation myocardial infarction (STEMI). Internationally many factors including female gender have been implicated, but no research has been conducted in Arab cultures. We aimed to explore the factors contributing to pre-hospital delay among female STEMI patients in Saudi Arabia. Method: This sequential, explanatory mixed methods study comprised a consecutive sample of 311 patients, presenting with STEMI to three hospitals in Riyadh, from March 2011–August 2011. Of these, 189 patients (36 females) were eligible and interviewed using the Response to Symptoms Questionnaire. A purposive sample of 18 patients (9 females) then participated in qualitative interviews that were taped and transcribed prior to thematic analysis. Findings: The median pre-hospital delay for males was 5 h and 12.9 h for females ( p <0.002). Standard multiple regression determined female gender as the strongest predictor of transfer delay–from decision to seek help to hospital arrival. Qualitative analysis produced five gender-related themes: (a) women require a male relative's permission to seek medical help; (b) women cannot travel to hospital unless accompanied by a male relative; (c) women prioritise family responsibilities over seeking help; (d) women lack knowledge of myocardial infarction (MI) symptoms and treatment; and (e) perception that women should not attract attention. Conclusion: This study provides new insight into how cultural factors increase pre-hospital delay for women within Saudi Arabia. While the quantitative data demonstrates that women experience much longer delays, the qualitative interviews confirm that cultural factors are implicated. Further research is urgently required.